Cover Image, Volume 53, Number 4, April 2018. Issue 4 (25th March 2018) - Uike, Kiyoshi; Nagata, Hazumu; Hirata, Yuichiro; Yamamura, Kenichiro; Terashi, Eiko; Matsuura, Toshiharu; Morihana, Eiji; Ohkubo, Kazuhiro; Ishii, Kanako; Sakai, Yasunari; Taguchi, Tomoaki; Ohga, Shouichi
Abstract : The cover image, by Kiyoshi Uike et al., is based on the Original Article Effective shunt closure for pulmonary hypertension and liver dysfunction in congenital portosystemic venous shunt, DOI:10.1002/ppul.23944 .